The impact of environmental factors on the infection of cereals with Fusarium species and mycotoxin production – a review - Sasho POPOVSKI; Franci Aco CELAR (Acta Agriculturae Slovenica)
Several phytopathogenic Fusarium species occurring worldwide on cereals as causal agents of ‘head blight’ (scab) of small grain cereals and ‘ear rot’ of maize, are capable of accumulating, in infected kernels, several mycotoxins some of which of notable impact to human and animal health. Fusarium graminearum, F. culmorum, F. poae, F. avenaceum and Microdochium nivale predominantly cause Fusarium diseases of small-grain cereals. Maize is predominantly attacked by F. graminearum, F. moniliforme, F. proliferatum and F. subglutinans. The review is focused on the influence of climatic variables, particularly temperature, humidity and rainfall on growth, reproduction, survival, competitive ability, mycotoxicity and pathogenicity of Fusarium fungi commonly isolated from wheat, barley and maize.